Menggali Inspirasi Dari Kisah Petrus: Strategi Efektif Dalam Memulihkan Motivasi Saat Menghadapi Keterpurukan - Setyaningsih, Sulis (Sekolah Tinggi Teologi Kanaan Nusantara, 2024)
The purpose of this paper is to help everyone who is experiencing a slump to get inspiration from the life story of the Disciple of the Lord Jesus named Peter. Everyone needs to realize that he is a special creation of God, namely having a mind. With this privilege, humans are expected to be able to think clearly and place themselves well when facing life's problems. But in fact this is not the case, some people tend not to be able to overcome their problems when they are in a slump. Some are able to recover but some are not. This depends on the particular person. This article is titled